The role of PD-1 signaling in health and immune-related diseases - Chen, Ru-Yue; Zhu, Yun; Shen, Yun-Yan; Xu, Qin-Ying; Tang, Han-Yun; Cui, Ning-Xun; Jiang, Lu; Dai, Xiao-Mei; Chen, Wei-Qing; Lin, Qiang; Li, Xiao-Zhong (Frontiers in Immunology, 2023)
Programmed cell death 1 receptor (PD-1) and its ligands constitute an inhibitory pathway to mediate the mechanism of immune tolerance and provide immune homeostasis. Significantly, the binding partners of PD-1 and its associated ligands are diverse, which facilitates immunosuppression in cooperation with other immune checkpoint proteins. Accumulating evidence has demonstrated the important immunosuppressive role of the PD-1 axis in the tumor microenvironment and in autoimmune diseases. In addition, PD-1 blockades have been approved to treat various cancers, including solid tumors and hematological malignancies. Here, we provide a comprehensive review of the PD-1 pathway, focusing on the structure and expression of PD-1, programmed cell death 1 ligand 1 (PD-L1), and programmed cell death 1 ligand 2 (PD-L2); the diverse biological functions of PD-1 signaling in health and immune-related diseases (including tumor immunity, autoimmunity, infectious immunity, transplantation immunity, allergy and immune privilege); and immune-related adverse events related to PD-1 and PD-L1 inhibitors.